Pengaruh Project-Based Learning Berbasis Scratch terhadap Motivasi Belajar Siswa pada Mata Pelajaran Informatika - Moh. Ilham Saputra Panigoro; Sitti Suhada; Arif Dwinanto; Nikmasari Pakaya; Indhitya R. Padiku (Inverted: Journal of Information Technology Education, 2026)
This study aims to determine the effect of the Scratch-based Project-Based Learning (PjBL) model on students' learning motivation in Informatics subjects at SMP Negeri 1 Mananggu. This research used a quasi-experimental method with a Pretest–Posttest Control Group Design. The research subjects consisted of 26 students divided into experimental and control classes. The research instrument used a learning motivation questionnaire based on the ARCS model, including Attention, Relevance, Confidence, and Satisfaction. Data analysis was conducted using descriptive and inferential statistics with the help of SPSS. The results showed that students' learning motivation in the experimental class increased significantly compared to the control class. The Independent Samples t-test showed a significance value of less than 0.05, indicating a significant difference between the two classes. The effect size value of 1.61 indicates a very large category. These findings indicate that the implementation of Scratch-based Project-Based Learning is effective in improving students' learning motivation in Informatics learning.